Disingenuous: The Latest Legal Challenges to Insurance Market Reforms - Hall, Mark A. (The Hastings Center report, 2014)
Not since the civil rights era has enacted national legislation been fought so fiercely as the Patient Protection and Affordable Care Act. Political, ideological, and social forces have mobilized to undermine the ACA at numerous fronts, including the Supreme Court, Congress, state governments, and the court of public opinion. The ACA has survived a constitutional challenge, a presidential re-election, numerous repeal votes in the House, and avowedly obstreperous state regulators. But it has not yet run the full gauntlet of lethal strategies. The latest line of attack is a collection of orchestrated lawsuits seeking to keep the federal exchange from paying any premium tax subsidies. What if the challengers eventually prevail? What would happen then?